Time Series Analysis of Vegetation Recovery After the Taum Sauk Dam Failure - Abree A. Peterson; Karen E. DeMatteo; Roger J. Michaelides; Stanton Braude; Alan R. Templeton (Remote Sensing)
On 14 December 2005, there was a catastrophic flood after a failure in the upper reservoir at the Taum Sauk Plant in southern Missouri. While there has been extensive research on the cause of the dam’s failure and the flood’s immediate impact, there has been limited investigation on how vegetation in and around the resulting flood scour has changed since this event. This study fills this gap through a time-series analysis using imagery sourced from GloVis and Planet Explorer to quantify vegetation levels prior to the flood (2005) through to 2024. Vegetation level was calculated using the Normalized Difference Vegetation Index (NDVI), which measures the level of greenness via light reflected by vegetation. Vegetation levels inside of the scour were compared to two 120 m buffer areas surrounding the scour, immediately adjacent (0–120 m) and at 120–240 m from the scour’s edge. Within the scour, NDVI analysis showed a dramatic loss of vegetation immediately after the flood, followed by varying levels for several years, before a steady increase in the proportion of areas with vegetation starting in 2014. The buffer area adjacent to the edge of the scour showed a similar pattern, but at lower magnitudes of change, which likely reflects the ragged edge created by the flood. The buffer area farther from the edge showed a consistent pattern of high vegetation, which likely reflects the broader landscape. While ground truthing confirmed these patterns between 2006 and 2011, in 2012, the ground truthing revealed much recovery in small local areas within the scour that were not apparent though NDVI analysis. These local areas of recovery were reflected in the pattern of recolonization of the scour from nearby glades (i.e., natural habitats of exposed bedrock) by glade flora and by the eastern collared lizard (Crotaphytus collaris collaris), an apex predator adapted to living in rocky, open areas and a bioindicator of vegetation recovery. While recovery of vegetation occurred steadily after 2012, ground truthing indicated that the original oak/hickory forest was now a minor component of this recovery, and that glade species dominated the former forested area.